Ruhao Dashi granules exert therapeutic effects on H1N1 influenza virus infection by altering intestinal microflora composition - Pan, Wei; Wu, Rui; Zhang, Qianyun; Ma, Yuan; Xiang, Jinxiang; Wang, Jingbo; Chen, Jing (Frontiers in Microbiology, 2024)
Objective: Antiviral medications for influenza could be ineffective due to the emergence of resistant influenza virus strains. Ruhao Dashi (RHDS) granules possess anti-inflammatory and antibacterial effects. The present study aimed to determine the efficacy of RHDS granules in treating influenza-infected mice and the mechanism underlying this treatment as well as its effect on the intestinal flora composition of the infected mice.The HPLC-UV method was used to identify the active components of RHDS granules. ICR mice were infected with influenza A virus (IAV) H1N1 subtype through a nasal drip. After the influenza mice model was successfully established, the pathological changes in the lungs were observed for 5 days after gavage treatment with 0.9% sterile saline and low, medium, and high doses (0.07, 0.14, and 0.28 g/mL, respectively) of RHDS granules. The serum levels of the cytokines IL-6 and TNF-α and sIgA were detected by ELISA. Real-time fluorescence quantitative PCR and western blotting assay were performed to determine the expression levels of the tight junction (TJ) proteins claudin-1, occludin, and zonula occludens-1 (ZO-1) in colon tissues. Furthermore, 16S rRNA gene sequencing of feces samples was conducted to assess the effect of RHDS granules on the gut microbiota.Results: RHDS granules exerted a protective effect on the lung tissues of IAV-infected mice; moreover, the granules reduced the synthesis of proinflammatory cytokines and increased the relative expression levels of claudin-1, occludin, and ZO-1 in colon tissues. Furthermore, RHDS granule treatment increased the relative abundance of Lactobacillus, Akkermansia, and Faecalibaculum and decreased the relative abundance of Muribaculaceae; thus, RHDS granules could stabilize the intestinal microbiota to some extent.RHDS granules exert a therapeutic effect on IAV-infected mice probably by modifying the structural composition of their intestinal microbiota.